Preparation of a preferentially oriented SAPO-34 membrane by secondary growth under microwave irradiation. Issue 61 (13th June 2016) - Bing, Liancheng; Wang, Guangjian; Wang, Fang; Liu, Xiufeng; Zhang, Baoquan
Abstract : A preferentially oriented SAPO-34 membrane with no large defects was prepared on an oriented SAPO-34 seed layer by secondary hydrothermal microwave growth. Abstract : Piece-like SAPO-34 crystals were directly assembled into a highly oriented seed layer on the α-Al2 O3 substrate by using spin-coating, and then a preferentially oriented SAPO-34 membrane with no large defects was prepared on an oriented SAPO-34 seed layer by secondary hydrothermal microwave growth. The synthesized membrane exhibited a high CO2 permeance of 1.57 × 10 −6 s −1 Pa −1 at 302 K and 138 kPa pressure drop, with a CO2 /CH4 separation selectivity of 109.